Impact of common genetic determinants of Hemoglobin A1c on type 2 diabetes risk and diagnosis in ancestrally diverse populations: A transethnic genome-wide meta-analysis - Wheeler E. (Public Library of Science, 2020)
10.1371/journal.pmed.1002383